PENGARUH KUALITAS LAYANAN DAN REPUTASI PERUSAHAAN TERHADAP KEPERCAYAAN SERTA DAMPAKNYA PADA KEPUASAN NASABAH (Studi Pada Nasabah Tabungan Bank Syariah Mandiri Cabang Kendal) - Irawan, Ade Candra; Tjahjaningsih, Endang (Jurnal Ilmiah Telaah Manajemen, 2016)
The purpose of this study to analyze and describe the influence of service quality and reputation of the trust as well as to analyze and describe the influence of service quality, corporate reputation and trust on customer satisfaction. Based on the purpose of the study, the researchers will conduct a study of research on the quality of service and the company's reputation of trust and the impact on customer satisfaction in customer savings at Bank SyariahMandiri Branch Kendal. In this study, the population is savings customers of Bank SyariahMandiri Branch Kendal until August 2015 that an unknown number of 13.245 customers. By using purposive sampling technique sampling is a way to determine the sample selection criteria of the respondents are already saving in Bank SyariahMandiri Branch Kendal more than one year can be sampled, then it is determined at 100 customers. Methods of data analysis using descriptive analysis, test instrument, namely the validity and reliability, test models and hypothesis testing. Of the analysts who conducted the study concluded that the quality of service partially positive and significant impact on the trust. Reputable companies partially positive and significant impact on the trust. Quality of service partially positive and significant impact on customer satisfaction. The company's reputation partially positive and significant impact on customer satisfaction. Belief in partial positive and significant impact on customer satisfaction. Belief does not mediate the effect of service quality and its reputation on customer satisfaction Keywords: service quality, company reputation, trust and customer satisfaction